Architectural pattern with half floral motifs and step-like figures - Temples of India Project Team (Jio Institute, 2024)
Debris from the original temple was salvaged when the current temple was reconstructed in the 1940s. These have been assembled in parts to form the jagati (raised platform). However, it is not known where they were located in the original temple. The architectural pattern used on the jagati or adhisthana of the temple with half floral motifs and step-like figures.